2016 Global Food Policy Report: Shifting the global food system - Ranganathan, Janet (2016)
Presentation by Janet Ranganathan, Vice President for Science and Research at World Resources Institute (WRI), at the launch of the 2016 Global Food Policy Report on March 31, 2016 in Washington, DC